Milk production of crossbred holstein × zebu on different pasture-management strategies (Bioscience Journal, 2020)
The objective of this study was to evaluate nutrient intake and digestibility, yield and components of milk from Holstein × Zebu cows on Tanzania grass pastures using a fixed-rest period or 95% light interception. The treatments consisted of evaluations of two Tanzania-grass pasture-management strategies: LI95 - when the pasture reached 95% light interception (LI), with 3 paddock-occupation days; and FR - the pasture was managed with a 30-days defoliation interval (DI) and 3 paddock-occupation days. Ten recently calved cows per treatment in year 1 and eight cows per treatment in year 2 were used, i.e. five cows per replicate in year 2 and four cows per replicate in year 2. Intake and digestibility of pasture nutrients, milk yield and milk composition were evaluated. The management strategies imposed on the Tanzania-grass pasture did not affect nutrient intake or digestibility. Milk yield and milk components were not affected by the management strategies, but milk yield per area unit was affected by the use of 95% light interception. The management strategy applying 95% light interception implies greater efficiency in the use of area, which translates to a higher milk yield per unit area, and thus it can be recommended to increase milk yield per area.